Roles of inflammasomes in viral myocarditis - Xu, Jingyu; Zhou, Zihao; Zheng, Yidan; Yang, Sai; Huang, Kun; Li, Huili (Frontiers in Cellular and Infection Microbiology, 2023)
Viral myocarditis (VMC), characterized by viral infection-induced inflammation, is a life-threatening disease associated with dilated cardiomyopathy or heart failure. Innate immunity plays a crucial role in the progression of inflammation, in which inflammasomes provide a platform for the secretion of cytokines and mediate pyroptosis. Inflammasomes are rising stars gaining increasing attention. The nucleotide oligomerization domain-, leucine-rich repeat-, and pyrin domain-containing protein 3 (NLRP3) inflammasome, the caspase recruitment domain-containing protein 8 (CARD8) inflammasome, and the caspase-11 inflammasome are three inflammasomes that were reported to affect the process and prognosis of VMC. These inflammasomes can be activated by a wide range of cellular events. Accumulating evidence has suggested that inflammasomes are involved in different stages of VMC, including the trigger and progression of myocardial injury and remodeling after infection. In this review, we summarized the pathways involving inflammasomes in VMC and discussed the potential therapies targeting inflammasomes and related pathways.